From the early days of unmanned aerial vehicles (UAVs) to their integration into wireless networks - Zoran M. Miličević (University of Defence in Belgrade, 2021)
Introduction/purpose: This paper provides an overview of Unmanned Aerial Vehicles (UAVs) from their early days to their integration into modern wireless networks. Methods: It analyzes, synthesizes and compares the UAVs development technologies throughout their history with significant aspects of their integration in wireless communication networks. Results: Important aspects of wireless communications as one of the key technologies for UAVs are presented. Next, energy efficiency as a research path for UAVs is considered. The paper also emphasizes the present state in this area as well as what the future of UAVs in communications will be. Conclusion: UAVs are important not only for widespread military usage in various combat operations and warfare environment, but also for other purposes such as their integration in 5G networks.